Performance of different categories of beef cattle finished in a feedlot regimen - Gottschall, Carlos S. (2005)
Data about 310 animals (150 younger steers (YS) fi nished between 12 and 14 months; 70 young steers (Y) fi nished between 20 and 22 months; and 90 cull cows (CC) from three to ten years were analyzed. The data were charted and analyzed in a MS Excel 97 spreadsheet. ADG was 1.004, 0.931 and 0.967 kg/day for YS, Y and CC, respectively. FC was 7.26; 10.55 and 11.61 kg MS ingested/kg weight gain, respectively for YS, Y and CC. Profi t was 25.19, 21.70 e 27.96 % for 151.6, 73.6 and 64.7 days of feedlot for YS, Y and CC, respectively. YS showed higher average daily gain and better feed : gain ration than Y and CC. The fi nishing of the different animal categories in a feedlot regimen resulted in an satisfactory economic return.